Improving the robustness of the advanced LIGO detectors to earthquakes. (5th November 2020) - Schwartz, E; Pele, A; Warner, J; Lantz, B; Betzwieser, J; Dooley, K L; Biscans, S; Coughlin, M; Mukund, N; Abbott, R; Adams, C; Adhikari, R X; et al.
Abstract: Teleseismic, or distant, earthquakes regularly disrupt the operation of ground–based gravitational wave detectors such as Advanced LIGO. Here, we present EQ mode, a new global control scheme, consisting of an automated sequence of optimized control filters that reduces and coordinates the motion of the seismic isolation platforms during earthquakes. This, in turn, suppresses the differential motion of the interferometer arms with respect to one another, resulting in a reduction of DARM signal at frequencies below 100 mHz. Our method greatly improved the interferometers' capability to remain operational during earthquakes, with ground velocities up to 3.9 μ m s −1 rms in the beam direction, setting a new record for both detectors. This sets a milestone in seismic controls of the Advanced LIGO detectors' ability to manage high ground motion induced by earthquakes, opening a path for further robust operation in other extreme environmental conditions.